2016
DOI: 10.5897/ijnam2015.0193
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of severe acute malnutrition and determinants of survival in Northern Ethiopia: A prospective cohort study

Abstract: Ethiopia has long history of food insecurity and nutritional problems affecting large proportion of the population caused by successive droughts. Despite of different interventions to tackle the problem there is no explicit data showing treatment outcome of the children generally in Ethiopia and specifically in the study area. Institutional based general prospective cohort study was employed. The respondents were 332 children of 6-59 months age admitted to Outpatient therapeutic program (OTP) providing health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 4 publications
5
12
2
Order By: Relevance
“…The median length of stay was (38.5 ± IQR 14 days) for recovered/cured children and this study was found to be in line with a multicentre, randomized intervention study done in Mali which showed that median recovery time of the entire cohort was 42 days. Another prospective cohort study conducted in southern people, nation and nationalities region of Ethiopia showed that the median recovery time was 49 days [18, 19]. However, the finding of this study found to be lower duration of stay in the outpatient therapeutic program than 92 days length of time to recovery a study done in Afar, Ethiopia [20].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The median length of stay was (38.5 ± IQR 14 days) for recovered/cured children and this study was found to be in line with a multicentre, randomized intervention study done in Mali which showed that median recovery time of the entire cohort was 42 days. Another prospective cohort study conducted in southern people, nation and nationalities region of Ethiopia showed that the median recovery time was 49 days [18, 19]. However, the finding of this study found to be lower duration of stay in the outpatient therapeutic program than 92 days length of time to recovery a study done in Afar, Ethiopia [20].…”
Section: Discussionmentioning
confidence: 61%
“…All SAM children between 6 and 59 months and admitted in the selected health facilities were included in the study. Sample size was determined using study conducted from Enderta district, Tigray, Northern Ethiopia, 2012 [18]. So, we calculate the sample size by medcalc©version 18.11.3 survival analysis (logrank test) at http://www.medcal.org [17].…”
Section: Methodsmentioning
confidence: 99%
“…[14] The finding in our study is consistent with that from a non-refugee population study in northern Ethiopia, which found that the majority of carers of children with SAM had a low literacy level. [15] In both SC programmes, the mean (SD) length of stay was longer than the recommended duration of 7 -10 days, [7] namely 10.4 (6) days at Ifo and 9.5 (4) days at Hagadera. Although no comparable studies were found for refugee populations, the finding reported here is consistent with that of a study among paediatric SAM inpatients conducted in northern India, which reported a mean (SD) length of stay of 11.7 (7.6) days.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Studies conducted in OTFPs in north and southwest Ethiopia and Yemen reported a mean length of stay of 45 days, 50 days and 40 days, respectively. [15,18,19] Although early discharge may be associated with relapses of SAM cases, longer stays in a CMAM programme, especially in the case of an OTFP, may be associated with defaulting. [7,20] The shorter stays observed in the OTFPs in this study may be attributed to early discharges following good responses to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research studies conducted in the country identified determinants of children's survival. Sex of child, medical comorbidities, treatment and follow-up status, and clinical diagnosis of SAM were associated to survival of children [1216]. The Ethiopian Ministry of Health established inpatient therapeutic feeding centers in the health facilities to reduce SAM-related mortalities of under-five children.…”
Section: Introductionmentioning
confidence: 99%